Promoter selectivity of Escherichia coli RNA polymerase: omega factor is responsible for the ppGpp sensitivity. - Igarashi, K (1989)
Transcription in vitro of stringently controlled Escherichia coli genes by purified RNA polymerase holoenzyme is inhibited by guanosine tetraphosphate (ppGpp). In order to examine possible role of omega factor in this ppGpp sensitivity, RNA polymerases with or without the omega factor were reconstituted and tested for their ppGpp sensitivity using an in vitro mixed transcription system. RNA polymerase lacking the omega factor was found virtually insensitive to ppGpp but the addition of a purified omega factor restored the ppGpp sensitivity of this omega-free RNA polymerase. These results raise a possibility that the omega factor is a regulatory protein of RNA polymerase and is involved in the ppGpp-mediated alteration of the promoter selectivity.